Новые библиографические технологии и проблемы их внедрения в социальное информационное обслуживание и библиографическую практику - Prokopčik, Marija (Knygotyra, 1988)
The article deals with the problem of the changing demands of education for librarianship and information work in developed capitalist countries as a result of the application of computers and changing technology of library work. There are indications that, under these conditions, education and training must be something rather different from traditional library education. The changing role of information, which becomes one of the natural resources of a country, and the rapid development of computer technology reveal new professional demands for librarians. They are becoming something like gatekeepers of information, mediators between information stored in databases and information users. As a result of this tendency, the teaching of online bibliographic searching is of great importance in the curricula of library schools all over the world. The main trends of alteration in the programs of library schools during the last 10 years are surveyed, and principal tendencies of future development in the education of librarians are revealed.